Public communication and political communication: for an interaction between citizenship and democracy - Nobre, Heloiza Helena Matos e; Nobre, Guilherme Fráguas (Organicom, 2013)
The purpose of the article is to establish the relationship of these six variables with one another: social capital, communication capital, public communication, political communication, citizenship and democracy. Basic assumptions are as follows: 1) social capital and communication capital enable public communication; 2) there is a transition from public communication (sphere of deliberation) to political communication (sphere of action); 3) citizenship, by involving those capitals and communications, would lead to participatory democracy (in contrast to representative democracy).